PETRA IV Workshop on Research with High-Energy X-rays at Ultra-Low Emittance Sources. Issue 3 (4th May 2017) - Ruett, U.; Dippel, A.-C.; Beckmann, F.; Lienert, U.; Liermann, H.-P.; Zimmermann, M. V.; Schroer, C. G.
Abstract : Recent advances in storage ring technology pioneered by MAX IV (Sweden) allow synchrotron radiation sources to achieve significantly smaller emittances than those currently in operation. This new, multi-bend achromat technology can thus boost spectral brightness, enabling unprecedented experimental possibilities. The high-energy synchrotron radiation facilities ESRF (France), SPring-8 (Japan), and APS (USA) have settled upgrade plans to improve their storage ring emittance by up to two orders of magnitude at 6 GeV electron energy. PETRA III at DESY has the largest circumference with 2.3 km. As the emittance scales favorably with the storage ring size, an upgrade of PETRA III offers the unique potential to reach a diffraction limit up to X-ray energies of 10 keV. Operating at 6 GeV with an emittance of 10 pmrad, this PETRA IV facility would pave the way for new experimental opportunities, especially for those using high photon energies.